The Problems of the Usage of the Term “Costs” in Accounting - Meškelienė, Audronė (Ekonomika, 1997)
The paper deals with the usage of the term “cost,” which describes costs in Lithuanian and foreign literature.The results obtained show that the terms used in Lithuanian language are defined and used differently even in official documents. Such use of terms causes a lot of difficulties, so it is necessary to unify the use of terms and define “costs” as a sacrifice made in order to obtain some good or service. An “expense” is the cost of an asset that has been used up or sold far the purpose of generating revenue.